2016
DOI: 10.1166/sam.2016.2993
|View full text |Cite
|
Sign up to set email alerts
|

Dental Applications of Nanodiamonds

Abstract: Nanodiamonds (NDs) have been used in various fields of medicine such as drug delivery, tissue regeneration and gene therapy. Although there has been research carried out investigated the potential of these remarkable materials in dentistry, to date no review has been published to summarize the studies conducted.Due to their target cell specificity, small size and fluorescence they have also been found to be usefulness in dentistry. Main applications of NDs in dentistry and medicine include guided tissue regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Their potential is under investigation for use in different therapy platforms in various fields of medicine, such as drug delivery, tissue regeneration, and gene therapy. Recent research also suggests that NDs could also be used as bioactive or antibacterial dental implant coatings [86,87]. However, no study has been found that incorporates NDs into dental restorative materials and which meets the inclusion criteria of the present review [86,87].…”
Section: Discussionmentioning
confidence: 97%
“…Their potential is under investigation for use in different therapy platforms in various fields of medicine, such as drug delivery, tissue regeneration, and gene therapy. Recent research also suggests that NDs could also be used as bioactive or antibacterial dental implant coatings [86,87]. However, no study has been found that incorporates NDs into dental restorative materials and which meets the inclusion criteria of the present review [86,87].…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies have revealed mechanical similarities between nano-hybrid and micro-hybrid materials based on filler types, morphologies, and volume fractions 36 . On the other hand, researchers have also reported superior18, 37, 38 or inferior39, 40 properties of micro-hybrid materials compared to nano-filled composites. Such variations are mainly due to the use of different characterisation techniques and parameters 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Nanocarbon family has superior physical and chemical properties and antibacterial effect 21 . Nanodiamonds (NDs) belong to the nanocarbon family and have advantages over other metal/metal-oxide nanoparticles for being more chemically stable, biocompatible, and not inducing cytotoxicity 22 . They are used in different fields of Medicine and Dentistry, including guided tissue regeneration, polymer reinforcement, and antibacterial dental implant coatings 22 , 23 …”
Section: Introductionmentioning
confidence: 99%